Kelimpahan Predator Benthik (Acanthaster planci) di Perairan Putri Menjangan, Kabupaten Buleleng, Bali - Oktiyas Muzaky Luthfi; Rizki Iliani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2020)
Pantai Putri Menjangan, has good condition of coral reef, is located at Gerokgak District, Buleleng, Bali. Natural threat came from other inventebrate such as the coral eater, Acanthaster planci, that prey on coral tissue. A. planci is from family Acanthasteridae has 7-12 arms covered by toxic spines with 25-35 cm of body diameter. The aim of this research was to know abundance of A. planci at Pantai Putri Menjangan. To observed abundance of this creatures, we performed a belt transect 10x30 m in 5 stations. All A. planci inside of transect was count, note color and their diameter. We also record types of substrates and coral lifeform in this location. The study showed the abundance of A. planci in stations 1-3 was lower about 0.0067 individu/m2 and higher in station 5 was 0.03 individu/m2. In conclusion that no outbreak sign in this location.